# Solve the Differential equations y'' + 4y = 4 tan^{2} x Question
Differential equations Solve the Differential equations $$y'' + 4y = 4 \tan^{2} x$$ 2021-02-22
We need to solve following differential equation
$$y" + 4y = 4 \tan^{2} x$$
Let us first solve the homogeneous part.
$$y" + 4y = 0$$
Let $$y = e^{m}x$$ be the trial solution. Then we get the auxiliary equation
$$m^{2} + 4 = 0$$
This gives us
$$m = \pm 2i$$
Thus the solution of the homogeneous part of the differential equation be
$$y_{h}(x) = c_{1} \cos(2x) + c_{2} \sin(2x)$$
We use variation of parameter to calculate a
particular solution y_h. Let us take
$$y_{1} = \cos 2x, y_{2} = \sin 2x$$
Then we get
$$y_{1} = -2 \sin 2x, y_{2} = 2 \cos 2x$$
The wro
ian of $$y_{1}\ and\ y_{2}$$ is
$$W = y_{1}y_{2} - y_{1}y_{2}$$
$$= (\cos 2x)(2 \cos 2x) - (-2 \sin 2x)(\sin 2x) = 2 \neq 0$$
In this case it is given that
$$f(x) = 4 \tan(2x)$$
Then by the formula we obtain
$$u_{1} = \int \frac{-y_{2}f}{W}dx$$
$$=\int \frac{-(\sin 2x)(4 \tan 2x)}{2}dx$$
$$=-2 \int \frac{\sin^{2}(2x)}{\cos(2x)}dx$$
$$=-2 \int (\frac{1- \cos^{2}2x}{\cos 2x})dx$$
$$=2 \int (\cos 2x- \sec 2x)dx$$
$$= 2 \int (\cos 2x - \sec 2x)dx$$
$$= \sin 2x - \ln |\sec 2x + \tan 2x|$$
Similarly
$$u_{2} = \int \frac{-y_{1}f}{W}dx$$
$$=\int \frac{(\cos 2x)(4 \tan 2x)}{2}dx$$
$$= 2 \int \sin(2x) dx$$
$$= -\cos (2x)$$
Thus by variation of parameters the patricular solution is
$$y_{p} = u_{1} y_{1} + u_{2} y_{2}$$
$$= (\sin 2x - \ln |\sec 2x + \tan 2x|)(\cos 2x) + (-\cos 2x)(\sin 2x)$$
$$y_{p} = -\cos 2x \ln |\sec 2x + \tan 2x|$$
Hence the general solution is
$$y = y_{c} + y_{p} = c_{1} \cos 2x + c_{2} \sin 2x - \cos 2x \ln |\sec 2x + \tan 2x|$$

### Relevant Questions Solve the Differential equations
$$\displaystyle{\frac{{{\left({d}^{{{2}}}\right)}{y}}}{\rbrace}}{\left\lbrace{d}{\left({t}^{{{2}}}\right\rbrace}+{4}{\left({\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{t}\right.}}}}+{3}{y}={e}^{{-{t}}}\right.}\right.}$$ Solve the Differential equations $$\displaystyle{\left({D}^{{3}}−{3}{D}+{2}\right)}{y}={0}$$ Solve the differential equations
(1) $$\displaystyle{x}{y}'-{2}{y}={x}^{{3}}{e}^{{x}}$$
(2) $$\displaystyle{\left({2}{y}{\left.{d}{x}\right.}+{\left.{d}{y}\right.}\right)}{e}^{{2}}{x}={0}$$ solve the Differential equations $$\displaystyle{y}{'''}+{10}{y}{''}+{25}{y}'={0}$$ Solve the Bernoulli Differential equations. $$\displaystyle{x}{y}′-{y}={x}{y}^{{5}}$$ Solve the given system of differential equations.
\[Dx+Dy+(D+1)z=0\)
Dx+y=e^{t}\)
Dx+y-2z=50\sin(2t)\) Give the correct answer and solve the given equation: $$\displaystyle{y}\ \text{ - 4y}+{3}{y}={x},{y}_{{1}}={e}^{x}$$ The coefficient matrix for a system of linear differential equations of the form $$\displaystyle{y}^{{{1}}}={A}_{{{y}}}$$ has the given eigenvalues and eigenspace bases. Find the general solution for the system.
$$\displaystyle{\left[\lambda_{{{1}}}=-{1}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{1}{0}{3}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{{2}}}={3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}-{i}{1}+{i}{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace},\lambda_{{3}}=-{3}{i}\Rightarrow\le{f}{t}{\left\lbrace{b}{e}{g}\in{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{2}+{i}{1}-{i}-{7}{i}{e}{n}{d}{\left\lbrace{b}{m}{a}{t}{r}{i}{x}\right\rbrace}{r}{i}{g}{h}{t}\right\rbrace}\right]}$$ Solve the differential equation $$2y"+20y'+51y=0, y(0)=2$$
$$y'(0)=0$$ Solve differential equation: $$\displaystyle{y}'+{y}^{{2}}{\sin{{x}}}={0}$$